2022
DOI: 10.3390/polym14102103
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility Kinetics of Polyhydroxyalkanoate and Poly(butylene succinate-co-adipate) after In Vitro Fermentation in Rumen Fluid

Abstract: Using polyhydroxyalkanoate (PHA) materials for ruminal boluses could allow for longer sustained release of drugs and hormones that would reduce administration time and unneeded animal discomfort caused by continuous administration. The objective of this study was to determine ruminal degradability and kinetics of biodegradable polymers and blends. A proprietary PHA-based polymer, poly(butylene succinate-co-adipate) (PBSA), PBSA:PHA melt blends, and forage controls were incubated in rumen fluid for up to 240 h.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The discovery of plastic-degrading capabilities within rumen microflora offers a promising new avenue for plastic waste management. Ruminant diets naturally include cutin, a plant polyester with structural similarities to some synthetic plastics (Galyon et al, 2022). This suggests that rumen microbes may have evolved enzymes capable of degrading certain types of plastics.…”
Section: Rumen Microflora: Biodegradation Warriorsmentioning
confidence: 99%
“…The discovery of plastic-degrading capabilities within rumen microflora offers a promising new avenue for plastic waste management. Ruminant diets naturally include cutin, a plant polyester with structural similarities to some synthetic plastics (Galyon et al, 2022). This suggests that rumen microbes may have evolved enzymes capable of degrading certain types of plastics.…”
Section: Rumen Microflora: Biodegradation Warriorsmentioning
confidence: 99%
“…Many thanks to Randy Chambers of William & Mary College (Williamsburg, VA, USA) for their assistance in the conceptualization of this work. The Animals 2023, 13, 928 13 of 14 authors acknowledge that the data contained within this article was previously published in a MSc thesis, "Ruminal Degradation of Polyhydroxyalkanoate and Poly(butylene succinate-co-adipate" [32].…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…We previously evaluated the in vitro ruminal degradation of PHA, PBSA, PBSA:PHA melt-blend, and low-density polyethylene (LDPE) polymers in rumen fluid for 10 days. This study demonstrated the potential for biodegradable polymers to begin the degradation process within 24 h in rumen fluid [10]. We further evaluated the in situ ruminal degradation of PHA, PBSA, PBSA:PHA, and LDPE films in dairy cattle for 150 d [11].…”
Section: Introductionmentioning
confidence: 95%
“…We previously evaluated in vitro digestion kinetics of PHA, PBSA, and a PBSA:PHA blend after fermentation in rumen fluid over 240 h ( Galyon et al, 2022 ). The results of that experiment indicated that the beginning stages of degradation may occur within 24 h of fermentation in rumen fluid.…”
mentioning
confidence: 99%
“…Compared with the results of our in vitro fermentation study of these products, in situ degradation was increased. In vitro degradation of PHA resulted in 0.53% mass loss by 10 d, with a fractional disappearance rate of 0.002%/h ( Galyon et al, 2022 ), whereas in situ degradation of PHA resulted in a remarkable 55% mass loss by 14 d and a fractional degradation rate of 7.84%/d.…”
mentioning
confidence: 99%